Some comments on the social origins of the Riel Protest of 1869 ... - Pannekoek, Frits, 1949- (Winnipeg: Pemmican Publications, 1979)
The English-speaking folk of Red River looked with excitement and hope on the debates that surrounded the confederation of the eastern provinces. The Protestant Canadians, arriving in vocal and visible numbers in the 1860s to farm along the Assiniboine and to trade in the small village of Winnipeg, provided ample evidence of the vigour that the new connection would bring. All were anxious that union be effected quickly and quietly. Even the Protestant English speaking mixed-bloods looked to Canada to pull Red River out of its morass of pettiness and squalor. When it became clear that Canada had secured the chartered land of the Hudson's Bay Company, most were ready, indeed anxious, to welcome the Canadian Governor, no matter how obnoxious he might be. (Metis) ...